Perancangan Interior Cafe dan Restoran Khas Surabaya di Jalan Embong Malang Surabaya - Hidayat, Deby Wahyu (Intra, 2015)
Culinary is a part of life that is closely related to the consumption of food or a lifestyle that cannot be separated from everyday life. Therefore culinary is very important in life. Surabaya is the second largest city after Jakarta, as a metropolitan city with the urban communities of globalization trend that requires café and restaurant in everyday life. Other than that, time becomes increasingly valuable and city life hustles and bustles in routines. In connection with that reason, man becomes inclined for things that are practical in meeting their needs. By collaborating these two things, the café and restaurant, it is expected to introduce a variety of foods and beverages in the city of Surabaya as well as designing and make real a café and restaurant which is able to make the visitors get familiar with some of the culinary history of the city of Surabaya, so that the visitors can not only enjoy the food and drinks of Surabaya typically, but also will be more familiar with the history of the food itself. In addition, visitors can also enjoy a café for hangout which is located in the the third floor outdoor area of the mall area to get a special sensation and to enjoy the served coffee and Surabaya city views from the top of the mall building.